ANALISIS HUKUM PERKAWINAN ANTARA ORANG PENGIDAP HIV/AIDS DALAM MUZAKARAH MUI No. 18 TAHUN 1996 (Studi Kasus Di KDS Soloplus) - Muhadi, Muhadi (Fakultas Syariah, Universitas Islam Negeri Raden Mas Said Surakarta, 2019)
Marriage is one of the religious orders for people who are able to do it immediately. Marriage is one of the Sunnatullah that applies to all of its creatures, especially humans. Marriage of HIV positive people is certainly different from marriage of healthy people in general, HIV positive household life is not as smooth as marriage in general, they will face different situations with normal partners, such as stigma and discrimination, the threat of contracting a virus from a partner, and boredom in taking ARV drugs. The purpose of this study was to know the household life of people living with HIV / AIDS in KDS Soloplus and the relevance of the marriage in Muzakarah MUI review No. 18 of 1996. This research is a qualitative field study. Data collection techniques using observation, interviews, and documentation. Data Analysis Techniques using descriptive analysis. The results of this study indicate that the household situation of people living with HIV / AIDS in the Soloplus peer group there are several problems that have been successfully observed and investigated including saturation of ARV drugs, fear of viruses that can infect their partners, adherence to religion, stigma and discrimination, and prohibitions on marriage people with HIV. Keywords: Marriage; Marriage of PLWHA; Household Situation of PLWHA Couples. Abstrak Pernikahan adalah salah satu perintah agama bagi orang-orang yang dapat melakukannya dengan segera. Pernikahan adalah salah satu Sunnatullah yang berlaku untuk semua makhluknya, terutama manusia. Perkawinan orang HIV positif tentu berbeda dengan perkawinan orang sehat pada umumnya, kehidupan rumah tangga HIV positif tidak semulus perkawinan pada umumnya, mereka akan menghadapi situasi berbeda dengan pasangan normal, seperti stigma dan diskriminasi, ancaman tertular virus dari pasangan, dan kebosanan dalam minum obat ARV. Tujuan dari penelitian ini adalah untuk mengetahui kehidupan rumah tangga orang yang hidup dengan HIV / AIDS di KDS Soloplus dan relevansi perkawinan dalam tinjauan Muzakarah MUI No. 18 tahun 1996. Penelitian ini adalah studi lapangan kualitatif. Teknik pengumpulan data menggunakan observasi, wawancara, dan dokumentasi. Teknik Analisis Data menggunakan analisis deskriptif. Hasil penelitian ini menunjukkan bahwa situasi rumah tangga orang yang hidup dengan HIV / AIDS dalam kelompok sebaya Soloplus ada beberapa masalah yang telah berhasil diamati dan diselidiki termasuk saturasi obat ARV, takut virus yang dapat menginfeksi pasangan mereka, kepatuhan terhadap agama, stigma dan diskriminasi, dan larangan menikah orang dengan HIV. Kata kunci: Perkawinan; Perkawinan ODHA; Situasi Rumah Tangga Pasangan ODHA.